Analisis Dan Evaluasi Sistem Drainase (Studi Kasus: Ruas Jl. Coklat, Kel. Bongkaran Kec. Pabean Cantikan, Kota Surabaya) - Wicaksono, Dimas Priatmoko; Harijianto, Didik; Asid, Nurul Jannah (Universitas Dr. Soetomo, 2020)
The city of Surabaya is one of the big cities in Indonesia. Like other cities, Surabaya also has problems, especially problems regarding flooding. The problem of flooding in the city of Surabaya can be classified into 2 (two). Namely, drainage problems due to natural factors and man-made. One of the roads that are still regularly flooded in Surabaya when it rains is Jalan Coklat. In this study the authors analyzed using secondary data from related agencies from field observations. These data include rainfall data, inundation data, tide data and dimensions of existing canals and other complementary structures. From these data, it can be obtained that the average rainfall value is 97.54 mm / day, the rain intensity is 214.88 mm / hour for the 10th period, while the Flood Debit Q Planning is 0.95 m3 / sec, and the discharge in the existing channel can be 0, 849 m3 / second. From the Tide Data, it is obtained that the peak of the tide is 150 cm high on December 13, 2016 and the lowest low tide is 130 cm on January 25, 2016. From the calculation and analysis results in the area that affects the occurrence of inundation is the channel dimension with Width: 50 x Height: 80 cm From the analysis of the calculation of the redesign using the box culvert, the dimensions of each box are obtained, namely the width of the box culvert: 80 x height: 100 x length: 120 cm for the 10th period with a capacity of 2.227 m3 / second. If the rainfall is high in the area and the water level in the Kalimas river is overflowing, the results of the analysis need to install a floodgate with the dimensions of the sluice gate Width: 60 x Height: 180 x Thickness: 1 cm so that when there is back water in the jl area . Brown floodgates function and when the rainfall is also high, the floodgates are already operating, so to reduce water puddles, it is necessary to use the help of a pump. From the analysis results, the pump capacity is 2.5 m3 / second.